Beginnings of literary criticism at the Universidad Nacional: Form and representations of poetic criticism in Repertorio Americano (1974-1982) - Montero Corrales, Cristopher (2023)
This article deals with the origins of critical-literary thought at the National University of Costa Rica from the magazine Repertorio Americano (1974-1982) as a way of understanding the movements of literary criticism and the form of critical thought and its ideological and literary representations in the Central American region. Specifically, it makes assessments regarding poetic literary criticism, theories, and methodologies. It understands literary criticism as a discursive-writing practice related to the formation of historical thought which, in turn, is closely intertwined with the context of its production and generator of meaning.